2020
DOI: 10.1111/epi.16779
|View full text |Cite
|
Sign up to set email alerts
|

Seizure control, stress, and access to care during the COVID‐19 pandemic in New York City: The patient perspective

Abstract: Objective Our epilepsy population recently experienced the acute effects of the COVID‐19 pandemic in New York City. Herein, we aimed to determine patient‐perceived seizure control during the surge, specific variables associated with worsened seizures, the prevalence of specific barriers to care, and patient‐perceived efficacy of epilepsy care delivered via telephone and live video visits during the pandemic. Methods We performed a cross‐sectional questionnaire study of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
78
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(90 citation statements)
references
References 27 publications
(24 reference statements)
6
78
5
1
Order By: Relevance
“…The results of our study are consistent with available reports suggesting that seizures in PWE are infrequently worsened by COVID-19 [3] , [14] , [15] . We noted seizure exacerbation in only one out of 17 patients with confirmed COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of our study are consistent with available reports suggesting that seizures in PWE are infrequently worsened by COVID-19 [3] , [14] , [15] . We noted seizure exacerbation in only one out of 17 patients with confirmed COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…Otherwise, our cohort was heterogenous in terms of epilepsy type, seizure frequency, pharmacotherapy, the presence of disabilities, comorbidities, and employment status. Similarly to other studies [3] , [6] , [14] , [15] , [16] , majority of patients reported limited access to health care during the pandemic.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Rosengard и соавт. [11] во время пандемии COVID-19 не сообщили об изменении контроля над приступами 75,1% пациентов, тогда как 17,5% сообщили, что их контроль над приступами ухудшился, только 7,3% сообщили об улучшении. Пациенты с подтвержденным или подозреваемым COVID-19 не сообщали об ухудшении контроля над приступами.…”
unclassified